2021
DOI: 10.1021/jacs.1c08177
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Cβ–H Functionalization of l-Arg and l-Leu in Nonribosomally Derived Peptidyl Natural Products: A Tale of Two Oxidoreductases

Abstract: Muraymycins are peptidyl nucleoside antibiotics that contain two Cβ-modified amino acids, (2S,3S)-capreomycidine and (2S,3S)-β-OH-Leu. The former is also a component of chymostatins, which are aldehyde-containing peptidic protease inhibitors thatlike muraymycinare derived from nonribosomal peptide synthetases (NRPSs). Using feeding experiments and in vitro characterization of 12 recombinant proteins, the biosynthetic mechanism for both nonproteinogenic amino acids is now defined. The formation of (2S,3S)-cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 69 publications
2
24
0
Order By: Relevance
“…This study, as well as previous ones, provides evidence that l ‐Cap is synthesized from l ‐Arg before incorporation into the NRPS machinery in CMN and VIO biosynthesis [13] . By contrast, the l ‐ epi ‐Cap moiety is synthesized after the precursor l ‐Arg incorporated into the NRPS machinery in muraymycin biosynthesis, where an unusual dehydrogenase catalyzes C β ‐N bond formation of l ‐Arg to form l ‐ epi ‐Cap [16] . The A domain of VioG (VioG‐A) in VIO biosynthesis was reported to specifically activates l ‐Cap [13] .…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…This study, as well as previous ones, provides evidence that l ‐Cap is synthesized from l ‐Arg before incorporation into the NRPS machinery in CMN and VIO biosynthesis [13] . By contrast, the l ‐ epi ‐Cap moiety is synthesized after the precursor l ‐Arg incorporated into the NRPS machinery in muraymycin biosynthesis, where an unusual dehydrogenase catalyzes C β ‐N bond formation of l ‐Arg to form l ‐ epi ‐Cap [16] . The A domain of VioG (VioG‐A) in VIO biosynthesis was reported to specifically activates l ‐Cap [13] .…”
Section: Resultssupporting
confidence: 71%
“…[13] By contrast, the l-epi-Cap moiety is synthesized after the precursor l-Arg incorporated into the NRPS machinery in muraymycin biosynthesis, where an unusual dehydrogenase catalyzes C β -N bond formation of l-Arg to form l-epi-Cap. [16] The A domain of VioG (VioG-A) in VIO biosynthesis was reported to specifically activates l-Cap. [13] CmnG-A and VioG-A share ~59 % amino acid sequence identity (Figure S9) and their 10-residue substrate-specificity sequences are highly conserved (90 %, Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The peptide scaffold of the muraymycins is assembled by NRPS enzymes (Mur12-Mur14, Mur21, Mur25 and Mur27). Recently, Mur22 was characterised as an FAD-dependent dehydrogenase: a cyclase that generates the epicapreomycidine residue via dehydrogenation and intramolecular cyclisation of L-Arg, while Mur15 was conrmed as a nonheme Fe 2+ -and aKG-dependent dioxygenase, generating 239 Interestingly, modications of L-Arg and Leu occur aer NRPS-mediated peptide chain extension. Since no lipase was found in the mur gene cluster, addition of the FA remains unknown.…”
Section: Lipoglycopeptidesmentioning
confidence: 99%
“…Recent advances have shown that capreomycidines can be divergently biosynthesized on NRPSs via dehydrogenation and thioester-mediated Michael addition reactions in the faulknamycin and muraymycin biosynthetic pathways. 10,11 Currently, cyclic arginine ncAAs have limited commercial availability due to their multiple synthetic steps and heavy reliance on protecting groups. 2 This has hampered an understanding of their role in establishing the bioactivities of their cognate NRPS products.…”
Section: Introductionmentioning
confidence: 99%